THEMATIC GROUPS OF ENGLISH AND UZBEK WORDS WITH A NOUN COMPONENT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Proverbs are linguists and representatives of many fields of linguistics. It is an object of constant study by historians and ethnographers. Proverb genre it has its own linguistic features that distinguish it from other genres features give the proverbs a melody, a beautiful meaning and the listener's help to focus on the speech.